Morphometric Indices and Venom Protein Profile in Different Populations of Androctonus crassicauda - Mohammad Bagher Ghavami; Zohreh Alibabaei; Fatemeh Ghavami (Journal of Arthropod-Borne Diseases, 2022)
Background: Androctonus crassicauda is the most medically relevant animal and understanding its morphological characteristics is essential in the production of antiscorpion sera.